Pleiotropic Effects of the Protease-Activated Receptor 1 (PAR1) Inhibitor, Vorapaxar, on Atherosclerosis and Vascular Inflammation - Julian Friebel; Eileen Moritz; Marco Witkowski; Kai Jakobs; Elisabeth Strässler; Andrea Dörner; Daniel Steffens; Marianna Puccini; Stella Lammel; Rainer Glauben; Franziska Nowak; Nicolle Kränkel; et al. (Cells, 2021)
Background: Protease-activated receptor 1 (PAR1) and toll-like receptors (TLRs) are inflammatory mediators contributing to atherogenesis and atherothrombosis. Vorapaxar, which selectively antagonizes PAR1-signaling, is an approved, add-on antiplatelet therapy for secondary prevention. The non-hemostatic, platelet-independent, pleiotropic effects of vorapaxar have not yet been studied. Methods and Results: Cellular targets of PAR1 signaling in the vasculature were identified in three patient cohorts with atherosclerotic disease. Evaluation of plasma biomarkers (n = 190) and gene expression in endomyocardial biopsies (EMBs) (n = 12) revealed that PAR1 expression correlated with endothelial activation and vascular inflammation. PAR1 colocalized with TLR2/4 in human carotid plaques and was associated with TLR2/4 gene transcription in EMBs. In addition, vorapaxar reduced atherosclerotic lesion size in apolipoprotein E–knock out (ApoEko) mice. This reduction was associated with reduced expression of vascular adhesion molecules and TLR2/4 presence, both in isolated murine endothelial cells and the aorta. Thrombin-induced uptake of oxLDL was augmented by additional TLR2/4 stimulation and abrogated by vorapaxar. Plaque-infiltrating pro-inflammatory cells were reduced in vorapaxar-treated ApoEko mice. A shift toward M2 macrophages paralleled a decreased transcription of pro-inflammatory cytokines and chemokines. Conclusions: PAR1 inhibition with vorapaxar may be effective in reducing residual thrombo-inflammatory event risk in patients with atherosclerosis independent of its effect on platelets.